Can eye of origin serve as a deviant? Visual mismatch negativity from binocular rivalry - van Rhijn, Manja; Roeber, Urte; O'Shea, Robert P. (Frontiers in Human Neuroscience, 2013)
The visual mismatch negativity (vMMN) is a negative deflection in an event-related potential (ERP) between 200 and 400 ms after onset of an infrequent stimulus in a sequence of frequent stimuli. Binocular rivalry occurs when one image is presented to one eye and a different image is presented to the other. Although the images in the two eyes are unchanging, perception alternates unpredictably between the two images for as long as one cares to look. Binocular rivalry, therefore, provides a useful test of whether the vMMN is produced by low levels of the visual system at which the images are processed, or by higher levels at which perception is mediated. To investigate whether a vMMN can be evoked during binocular rivalry, we showed 80% standards comprising a vertical grating to one eye and a horizontal grating to the other and 20% deviants, in which the gratings either swapped between the eyes (eye-swap deviants) or changed their orientations by 45° (oblique deviants). Both standards and deviants were shown for 400 ms followed by 100 ms of a dark screen. Fifteen participants observed the stimuli in 16, 4-minute blocks. In 8 consecutive blocks, participants recorded their experiences of rivalry by pressing keys—we call this the attend-to-rivalry condition. In the remaining 8 consecutive blocks, participants performed a demanding task at fixation (a 2-back task), also by pressing keys—we call this the reduced-attention condition. Starting condition was randomised across participants. We found a vMMN to oblique deviants that was similar during attend-to-rivalry conditions and during reduced-attention conditions. Critically, we found a similar vMMN to eye-swap deviants. We conclude that the vMMN can be evoked during the ever-changing perceptual changes of binocular rivalry and that it is sensitive to the eye of origin of binocular-rivalry stimuli. This is consistent with the vMMN’s being produced by low levels of the visual system.